Decree-Law Of The President Of The Republic No. 101 Of The Year 2012 On Amending Some Provisions Of The Income Tax LawIssued As Per Law No. 91 Of The Year 2005 And The Determination Of Some Tax Facilities, Contribution To The Achievement Of Social Justice And Limiting Tax Evasion Incidents &Law No. 11 Of The Year 2013 On The Amendment Of Some Provisions Of The Income Tax Law Promulgated By Law No. 91/2005 And Amendments Thereof As Amended By The Decree-Law N - Egypt (2025)
Decree-Law of the President of the Republic No. 101 of the Year 2012 on amending Some Provisions of the income tax law issued as per law no. 91 of the year 2005 and the determination of some tax facilities, contribution to the achievement of social justice and limiting tax evasion incidents – law no. 11 of the year 2013 on the amendment of Some Provisions of the income tax law Promulgated by law no. 91 of the year 2005 and amendments thereof as amended by the decree-law no. 101 of the year 2012 قرار رئيس جمهورية مصر العربية بالقانون رقم 101 لسنة 2012 بتعديل بعض أحكام قانون الضريبة على الدخل الصادر بالقانون رقم 91 لسنة 2005 وتقرير بعض التيسيرات الضريبية والمساهمة فى تحقيق العدالة الاجتماعية والحد من حالات التهرب الضريبى -- قانون رقم 11 لسنة 2013 بشأن تعديل بعض أحكام قانون الضريبة على الدخل الصادر بالقانون رقم 91 لسنة 2005 وتعديلاته والمعدل بالقرار بقانون رقم 101 لسنة 2012